Sparks, Kenton L. Ethnicity and Identity in Ancient Israel. Prolegomena to the Study of Ethnic Sentiments and their Expression in the Hebrew Bible. Winona Lake, Indiana: Eisenbrauns, 1998. 331 pp. - Magneres, Magdalena (Estudios de Asia y África, 2000)
-